Phosphodiesterase 4 Inhibitors in Immune-mediated Diseases: Mode of Action, Clinical Applications, Current and Future Perspectives - I. Sakkas, Lazaros; Mavropoulos, Athanasios; P. Bogdanos, Dimitrios (Current Medicinal Chemistry, 2017)
Phosphodiesterase (PDE) 4 is a superfamily of enzymes that catalyze the hydrolysis of cyclic adenosine 3',5'-monophosphate (cAMP), an intracellular second messenger and regulator of a wide array of genes and proteins. Increased levels of intracellular cAMP lead to activation of genes but also to inhibition of nuclear factor-kappa B, involved in pro-inflammatory responses. By increasing cAMP levels, PDE4 inhibitors, such as apremilast, reduced production of pro-inflammatory TNFα, IFNγ, and IL-17 and increased production of anti-inflammatory IL-10 in lipopolysaccharide-stimulated peripheral blood mononuclear cells, and in patients with psoriatic arthritis (PsA). Among PDE4 inhibitors, apremilast, roflumilast, and crisabolore have been approved for the treatment of psoriasis and PsA, chronic obstructive pulmonary disease, and atopic dermatitis, respectively. In a preliminary study on psoriasis and PsA we showed that at 6 months apremilast decreased IFNγ+CD3+ Th1 cells and IL- 17+CD3+ Th17 cells and increased regulatory B cells and regulatory T cells. In this review, we highlight recent findings of PDE4 inhibitors in atopic dermatitis, alopecia areata, uveitis, rheumatoid arthritis, psoriasis and PsA, systemic lupus erythematosus, vasculitis, systemic sclerosis, multiple sclerosis and inflammatory bowel disease. Given the role of cAMP as second messenger in diverse intracellular pathways, selective PDE4 inhibitors are likely to be therapeutic agents for various immune mediated diseases.
Keywords: bregs